Pelatihan Pencatatan Keuangan Sederhana Melalui Aplikasi Akuntansi Bersama Mitra Eskabeh Pamulang - Setianingsih, Setia; Muanifah, Suciati; Finatariani, Endah (Abdimisi, 2025)
Community service is one of the manifestations of the Tri Dharma of Higher Education that bridges community needs with academic competencies. Pamulang University, through the Accounting Study Program, in collaboration with Mitra Eskabeh Pamulang, carried out an assistance program for Micro, Small, and Medium Enterprises (MSMEs) in Bambu Apus, Pamulang. The main problems faced by the partners were limited understanding of accounting, the absence of separation between business and personal finances, minimal transaction recording, and a lack of knowledge regarding the Break Even Point (BEP) as a basis for profit planning.The program was conducted on April 24–26, 2025, using lectures, discussions, practical sessions, and sharing sessions. The materials included the preparation of simple financial statements, cash flow recording, cost of production calculation, and BEP training. Monitoring and evaluation were carried out through online mentoring to ensure continuous consultation.The results showed significant improvement. Participants began to understand the function of financial statements as a basis for decision-making, separate business and personal assets, and prepare simple financial records. BEP training provided positive impacts, enabling participants to determine the break-even point, plan sales targets, and set selling prices more rationally. Beyond technical skills, the activity also fostered awareness of the importance of systematic financial recording and the use of digital applications to support business management.  Keywords: MSMEs, Community Service, Accounting, Break Even Point